2016
DOI: 10.1016/j.cej.2015.10.082
|View full text |Cite
|
Sign up to set email alerts
|

Promotional effect of microwave hydrothermal treatment on the low-temperature NH3-SCR activity over iron-based catalyst

Abstract: Microwave hydrothermal was introduced into the preparation of iron-cerium-titanium mixed oxide catalyst for NH 3-SCR of NO x , And the catalysts after microwave hydrothermal treatment or not are characterized by X-ray diffraction(XRD), Infrared spectrum(IR), Transmission Electron Microscope(TEM), nitrogen adsorption-desorption and temperature programmed desorption(NH 3 /NO-TPD). Microwave hydrothermal treatment enhanced the low-temperature NH 3-SCR activity of iron-cerium-titanium mixed oxide catalyst, and mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Fe-containing catalysts, such as Fe/SSZ-13, are active for the NH 3 -SCR of NO x [5,6]. Recently, Fe-Ti spinel has been developed as an environmentally benign SCR catalyst, which showed excellent activity and selectivity at 300-400°C [7].…”
Section: Introductionmentioning
confidence: 99%
“…Fe-containing catalysts, such as Fe/SSZ-13, are active for the NH 3 -SCR of NO x [5,6]. Recently, Fe-Ti spinel has been developed as an environmentally benign SCR catalyst, which showed excellent activity and selectivity at 300-400°C [7].…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal and precious metal oxides are often used as activity components of catalysts such as MnO x , VO x , CoO 3 , CuO x , FeO x , and CeO 2 . MnO x and FeO x exhibit an outstanding low‐temperature SCR activity, strong oxygen storage capacity and redox property, changeable valences, low cost, and lack of toxicity …”
Section: Introductionmentioning
confidence: 99%
“…11 MnO x and FeO x exhibit an outstanding low-temperature SCR activity, strong oxygen storage capacity and redox property, changeable valences, low cost, and lack of toxicity. 12,13 Particularly, MnO x -based catalysts have attracted considerable attention owing to good redox properties and excellent oxygen migration ability, which are beneficial for oxidation of NO to NO 2 , and the coexistence of NO and NO 2 could lead to a relatively high conversion of NO x at low temperature through a "fast NH 3 -SCR" reaction. 14,15 Qi and Yang 5 found that 10% Mn-15% Fe/TiO 2 catalyst had excellent activity and N 2 selectivity, and the NO conversion achieved 85% at 120°C.…”
Section: Introductionmentioning
confidence: 99%
“…17 It was reported that the oxides of Mn and Fe have good redox properties and oxygen storage capacities due to their changeable valences, low cost and lack of toxicity, especially for outstanding low-temperature SCR activity. 18,19 Peña et al 20 revealed that NO conversion on Mn/TiO 2 catalysts was approximately 100% at 140 °C, and the selectivity of N 2 was excellent at 120 °C. Zhu et al 17 prepared a series of Fe-Mn/TiO 2 catalysts with holmium (Ho) and found that Fe 0.3 Ho 0.1 Mn 0.4 /TiO 2 catalysts with a molar ratio of 1:10 (Ho:Ti) had the highest low-temperature SCR activity among these catalysts, and NO x conversion was 90% when temperatures were in the range of 120 to 200 °C.…”
Section: Introductionmentioning
confidence: 99%